English Teachers’ Perception of Using Technology in Teaching English in Merauke - Marni Bawawa (KOLONI, 2022)
The advance in technology has brought changes to every aspect of life including education. Various technology appliances and applications offer many helpful resources and techniques for teachers and learners to choose from in assisting their teaching and learning processes. Not only that it helps teachers to become more creative, it also  encourages more motivation for the learners. The successful of its application closely related to the way it is perceived by the users. In this sense, the teachers’ perceptions as the facilitator of knowledge in the class are worth exploring. This study therefore, investigated the perception of English teachers in Merauke in teaching English using technology. The data were obtained from six English teachers from four different junior high schools in Merauke through questionnaire and interview. The perceptions were categorized based on four acceptance aspects in the use of technology (UTAUT), performance, effort, and social expectations and facilitating conditions. The findings showed positive responses from the teachers regarding the use of technology in English teaching and learning. Pedagogical implications and suggestions for further study are discussed as well. Keywords: teachers’ perception, teaching English, technology, UTAUT